Electrode and preparation method and application thereof

CN119800424APending Publication Date: 2025-04-11HUANENG CLEAN ENERGY RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411974301.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art has problems such as low catalytic activity of the electrode, poor corrosion resistance, unstable electrode structure and short service life in the electrolytic hydrogen production of alcohol-containing wastewater.

Method used

A nickel substrate is used as the electrode substrate, and a first composite metal material layer formed by metal iron, metal nickel and metal cobalt is attached to the surface, and a second material layer of metal platinum is attached. Each metal layer is deposited through electrodeposition technology to optimize the composition and structure of the electrode material.

Benefits of technology

The corrosion resistance and catalytic activity of the electrode in alcohol-containing wastewater is improved, the operation life of the cathode electrode is extended, the operating efficiency of the reactor is improved, and the energy consumption per unit of hydrogen production is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800424A_ABST
    Figure CN119800424A_ABST
Patent Text Reader

Abstract

The invention discloses an electrode and a preparation method and application thereof, and belongs to the technical field of electrode materials. The electrode comprises a nickel base material; a first material layer is attached to the surface of the nickel substrate; a second material layer is attached to the surface of the first material layer; the first material layer is made of composite metal formed by iron, nickel and cobalt; and the second material layer is made of platinum. The preparation method of the electrode comprises the following steps: S1, taking a nickel base material as an electrode base material, and pretreating the nickel base material to obtain a pretreated nickel base material; s2, a metal iron element, a metal nickel element and a metal cobalt element are deposited on the pretreated nickel base material at the same time through electro-deposition treatment I, and the nickel base material loaded with the composite metal is obtained; and S3, depositing a metal platinum element on the nickel base material loaded with the composite metal by adopting electro-deposition treatment II to obtain the electrode. The electrode provided by the invention has the advantages of high catalytic activity, corrosion resistance and good stability, is particularly suitable for the alcohol-containing wastewater hydrogen production electrode, and is high in hydrogen production efficiency and low in energy consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrode materials, and in particular to an electrode and a preparation method and application thereof. Background Art

[0002] Under the severe challenges of global energy and environmental issues today, it is particularly important to find efficient and clean energy production methods. As one of the clean energy sources with the greatest development potential, hydrogen energy has the advantages of wide sources, high combustion calorific value, zero carbon emissions, diverse transportation forms, and large-scale distributed use, and therefore has attracted widespread attention. Among them, water electrolysis to produce hydrogen is one of the important ways to achieve "green hydrogen" production, but the traditional water electrolysis method of hydrogen production has problems such as high water consumption, high treatment costs, and poor corrosion resistance of electrode materials. Especially in industrial applications, the shortage of fresh water resources and large wastewater discharge have become key factors restricting its development.

[0003] On the other hand, in the industrial production processes such as chemical industry, petroleum refining, textile printing and dyeing, a large amount of high-chroma, high-chemical oxygen demand (COD) wastewater containing alcohol organic matter will be produced. If these wastewaters are discharged directly without treatment, they will seriously pollute the environment and pose a threat to human health and the ecosystem. Therefore, it is of great economic and social value to develop a technology that can not only treat these alcohol-containing wastewaters but also efficiently produce hydrogen. In recent years, researchers have begun to explore methods for producing hydrogen by electrolysis of industrial wastewater to achieve resource utilization of wastewater and reduce emissions. However, due to the complex composition and low conductivity of industrial wastewater, traditional electrolysis hydrogen production processes face problems such as short electrode life, low catalytic efficiency, and high energy consumption when treating such wastewater. These problems are particularly prominent when treating alcohol-containing wastewater with high COD and high chroma.

[0004] Therefore, the development of an efficient and corrosion-resistant electrode material and its synthesis method is of great significance for the electrolysis of alcohol-containing wastewater to produce hydrogen. This electrode not only needs to be able to serve for a long time in a harsh corrosive environment, but also needs to have good catalytic activity of both cathode and anode, and can efficiently degrade organic matter in wastewater and produce hydrogen at the same time. Summary of the invention

[0005] The main purpose of the present application is to provide an electrode and a preparation method and application thereof, so as to solve the problem of low electrode catalytic activity in the electrolysis of alcohol-containing wastewater to produce hydrogen in the prior art.

[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present application, an electrode is provided, which includes a nickel substrate, a first material layer is attached to the surface of the nickel substrate, and a second material layer is attached to the surface of the first material layer; wherein the material of the first material layer is a composite metal formed by metallic iron, metallic nickel and metallic cobalt; and the material of the second material layer is metallic platinum.

[0007] Furthermore, the nickel substrate is nickel foam or nickel mesh.

[0008] Furthermore, the thickness of the nickel substrate is 0.2 to 5.0 mm.

[0009] Furthermore, the thickness of the first material layer is 1 to 8 mm.

[0010] Furthermore, the thickness of the second material layer is 0.01-0.1 mm.

[0011] Furthermore, the particle size of the metal iron, metal nickel or metal cobalt is 0.1 to 1 μm.

[0012] Furthermore, the particle size of the metal platinum is 0.1 to 0.5 μm.

[0013] According to a second aspect of the present application, a method for preparing the above-mentioned electrode is provided, comprising the following steps:

[0014] Step S1: using a nickel substrate as an electrode substrate, pretreating the nickel substrate to obtain a pretreated nickel substrate;

[0015] Step S2: using electrodeposition treatment I to simultaneously deposit metallic iron, metallic nickel and metallic cobalt on the pretreated nickel substrate to obtain a nickel substrate loaded with composite metals;

[0016] Step S3: using electrodeposition treatment II to deposit metal platinum on the nickel substrate loaded with the composite metal to obtain an electrode.

[0017] Furthermore, in step S1, the nickel substrate is nickel foam or nickel mesh.

[0018] Furthermore, the thickness of the nickel substrate is 0.2 to 5.0 mm.

[0019] Furthermore, the pretreatment includes process I or process II; process I includes: placing the nickel substrate in an acid solution for static treatment to remove the oxide layer on the surface of the nickel substrate; process II includes: annealing the nickel substrate in a protective atmosphere to remove the oxide layer on the surface of the nickel substrate.

[0020] Furthermore, in process I, the acid solution is a hydrochloric acid solution; the molar concentration of the hydrochloric acid solution is 3 to 6 M, and the treatment time is 30 to 60 min.

[0021] Furthermore, in process II, the heating rate of the annealing treatment is 5-10°C / min, the temperature of the annealing treatment is 450-550°C, and the treatment time is 1.5-3h.

[0022] Furthermore, in process II, the protective atmosphere is composed of 85% to 95% argon and 5% to 15% hydrogen, calculated in volume percentage.

[0023] Furthermore, in step S2, the electrodeposition treatment I adopts a two-electrode system; wherein the nickel substrate is used as the working electrode; the platinum material is used as the counter electrode; and the mixed solution of iron salt, nickel salt, cobalt salt and water is used as the electrodeposition solution I.

[0024] Furthermore, the DC current density of the electrodeposition treatment I is 20 to 100 mA / cm 2 , the voltage is 2~10V.

[0025] Furthermore, the deposition time of the electrodeposition treatment I is 30 to 60 minutes.

[0026] Furthermore, the temperature of the electrodeposition solution I is 60-80°C.

[0027] Furthermore, the molar concentration of the electrodeposition solution I is 0.1-0.5 mol / L.

[0028] Furthermore, the mass ratio of iron salt, nickel salt and cobalt salt is (2-5):(3-10):(1-10).

[0029] Furthermore, the iron salt is iron nitrate or iron chloride.

[0030] Furthermore, the nickel salt is nickel nitrate or nickel chloride.

[0031] Furthermore, the cobalt salt is cobalt nitrate or cobalt chloride.

[0032] Furthermore, the platinum material is a platinum plate or a platinum mesh.

[0033] Furthermore, in step S3, the electrodeposition treatment II adopts a three-electrode system, wherein the nickel substrate loaded with the composite metal is used as the working electrode; graphite is used as the counter electrode; saturated calomel is used as the reference electrode; and a platinum salt solution is used as the electrodeposition solution II.

[0034] Furthermore, the DC current density of the electrodeposition treatment II is 10 to 50 mA / cm 2 , the voltage is 2~10V.

[0035] Furthermore, the deposition time of the electrodeposition treatment II is 50 to 150 minutes.

[0036] Furthermore, the temperature of the electrodeposition solution II is 30°C to 60°C.

[0037] Furthermore, the molar concentration of the electrodeposition solution II is 0.001-0.01M.

[0038] Furthermore, the weight ratio of the total weight of the iron salt, the nickel salt and the cobalt salt to the platinum salt is (100-500):1.

[0039] Furthermore, the platinum salt solution is at least one of potassium chloroplatinate solution, ammonium chloroplatinate solution, potassium chloroplatinite solution, sodium chloroplatinite solution, ammonium chloroplatinite solution and chloroplatinic acid solution.

[0040] According to a third aspect of the present application, a method for producing hydrogen from alcohol-containing wastewater is provided, wherein the electrodes for electrolyzing water in the hydrogen production method include an anode electrode and a cathode electrode; wherein the cathode electrode is the above-mentioned electrode, and the anode electrode is a graphite electrode.

[0041] According to a fourth aspect of the present application, there is provided application of the above electrode or the electrode prepared by the above preparation method in hydrogen production from alcohol-containing wastewater.

[0042] By applying the technical solution of the present application, an electrode and a preparation method and application thereof are provided, which improves the corrosion resistance, catalytic activity and stability of the electrode material by optimizing the composition and structure, and improves the operating life and stability of the cathode electrode in hydrogen production from alcohol-containing wastewater, thereby improving the operating efficiency of the reactor and reducing key parameters such as the unit energy consumption of hydrogen production. This technology provides new ideas and methods for coupling industrial wastewater treatment with water electrolysis to produce hydrogen, and has important application prospects and promotion value. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0044] Figure 1 A scanning electron microscope image of the electrode structure prepared in Example 1 of the present application is shown. DETAILED DESCRIPTION

[0045] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below in conjunction with the embodiments and drawings.

[0046] As described in the background technology, the electrode structure and active material design currently used for hydrogen production from alcohol-containing wastewater are unreasonable, and the preparation methods are different, resulting in low efficiency, poor corrosion resistance, unstable electrode structure and short service life of the electrode when electrolyzing hydrogen from alcohol-containing wastewater.

[0047] Therefore, according to one aspect of the present application, an electrode is provided, which includes a nickel substrate, a first material layer attached to the surface of the nickel substrate, and a second material layer attached to the surface of the first material layer; wherein the material of the first material layer is a composite metal formed by metallic iron, metallic nickel and metallic cobalt; and the material of the second material layer is metallic platinum.

[0048] The present application adopts four metal elements as active ingredients for electrolyzing water, and arranges nickel, cobalt and iron on the surface of a nickel substrate, and further arranges a layer of platinum metal material on the surface of the composite metal; through a two-layer structural design and the use of different metal elements in each layer, by optimizing the composition and structure of the electrode material, the corrosion resistance of the electrode in industrial alcohol-containing wastewater, the catalytic activity in hydrogen production from water electrolysis and the structural stability used as an electrode are improved, and the operating life and stability of the cathode electrode in hydrogen production from alcohol-containing wastewater are improved, thereby improving the operating efficiency of the reactor and reducing key parameters such as the unit energy consumption of hydrogen production.

[0049] In some embodiments, the nickel substrate is nickel foam or nickel mesh; the thickness of the nickel substrate is 0.2-5.0 mm, for example, any value among 0.2 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, or any range between two values. Using nickel of this thickness as the electrode substrate has good conductivity and better effect of electrodeposition of metal elements.

[0050] In some embodiments, the thickness of the first material layer is 1 to 8 mm, for example, any value among 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, or a range between any two of them; the thickness of the second material layer is 0.01 to 0.1 mm, for example, any value among 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 mm, or a range between any two of them.

[0051] In some embodiments, the particle size of metal iron, metal nickel, and metal cobalt is 0.1-1 μm, such as any value in 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0 μm, or any range between two values; the particle size of metal platinum is 0.1-0.5 μm, such as any value in 0.1, 0.2, 0.3, 0.4, 0.5 μm, or any range between two values. By controlling the particle size of each metal within the above range, the uniformity, adhesion, wear resistance, conductivity, and mechanical properties of the metal deposition layer can be improved.

[0052] In some embodiments, the mass ratio of the composite metal to the metal platinum is (500-1000):1; for example, any value among 500:1, 600:1, 700:1, 800:1, 900:1, 1000:1 or any range between two values. The mass ratio of the metal iron, metal nickel and metal cobalt in the composite metal is (2-5):(3-10):(1-10); in this mass ratio, the mass ratio of the metal iron is any value among 2, 3, 4, 5, the mass ratio of the metal nickel is 3, 4, 5, 6, 7, 8, 9, 10, and the mass ratio of the metal cobalt is 1, 2, 3, 4, 5, 6, 7, 8, 9, 10.

[0053] According to a second aspect of the present application, a method for preparing the above-mentioned electrode is provided, comprising the following steps:

[0054] Step S1: using a nickel substrate as an electrode substrate, pretreating the nickel substrate to obtain a pretreated nickel substrate;

[0055] Step S2: using electrodeposition treatment I to simultaneously deposit metallic iron, metallic nickel and metallic cobalt on the surface of the pretreated nickel substrate to obtain a nickel substrate loaded with composite metals;

[0056] Step S3: using electrodeposition treatment II to deposit metal platinum on the surface of the nickel substrate loaded with the composite metal to obtain an electrode.

[0057] The present application uses electrodeposition to deposit various metal elements on a nickel substrate. The active metal has stronger adhesion to the nickel substrate, the prepared electrode structure is more stable, and it also helps to ensure the service life of the electrode. Iron, nickel and cobalt are first electrodeposited on a nickel substrate, and then platinum is electrodeposited. These four metal elements are selected for deposition and the order of deposition is designed, which ultimately makes the prepared electrode structure more stable, has strong corrosion resistance and high catalytic activity, thereby improving the efficiency of hydrogen production from alcohol-containing wastewater.

[0058] In some embodiments, the nickel substrate is selected from nickel foam or nickel mesh with a thickness of 0.2 mm to 5.0 mm; the nickel substrate is then pretreated, and the pretreatment includes process I or process II; process I includes: placing the nickel substrate in an acid solution for static treatment to remove the oxide layer on the surface of the nickel substrate; process II includes: annealing the nickel substrate in a protective atmosphere to remove the oxide layer on the surface of the nickel substrate. Pretreatment of the surface of the nickel substrate to remove the oxide layer is helpful for subsequent metal deposition operations on the nickel surface, ensuring the deposition quality and the adhesion strength of the metal on the nickel substrate, thereby ensuring the stability of the electrode structure and the catalytic activity.

[0059] In some embodiments, in process I, the acid solution is a hydrochloric acid solution; the molar concentration of the hydrochloric acid solution is 3 to 6 M, for example, 3, 4, 5, 6 M, and the treatment time is 30 to 60 min, for example, 30, 40, 50, 60 min; the use of a hydrochloric acid solution of this concentration and this treatment time helps to remove the oxide layer of the nickel layer, further ensuring the subsequent electrodeposition effect and the adhesion stability of the deposited elements on the nickel substrate.

[0060] In some embodiments, in process II, the protective atmosphere is composed of 85% to 95% argon and 5% to 15% hydrogen, measured by volume percentage; in the protective atmosphere, the heating rate of the annealing treatment is 5 to 10° C. / min, and the temperature of the annealing treatment is 450 to 550° C., for example, 450° C., 500° C., and 550° C. The above annealing conditions can better remove the oxide layer or impurities on the surface of the nickel substrate to ensure the subsequent deposition effect on the surface of the nickel substrate and the adhesion strength of the deposited metal on the nickel substrate, thereby contributing to electrode stability and catalytic activity.

[0061] In some embodiments, in step S2, the electrodeposition treatment I adopts a two-electrode system, wherein the nickel substrate is used as the working electrode, the platinum material is used as the counter electrode, and the mixed solution of iron salt, nickel salt, cobalt salt and water is used as the electrodeposition solution I. By mixing the three metal salt solutions as the electrodeposition solution, it is possible to simultaneously electrodeposit iron, nickel and cobalt on the nickel substrate of the working electrode; when depositing the three metals of iron, nickel and cobalt, only by adopting the simultaneous deposition method can it be ensured that a composite metal layer composed of iron, nickel and cobalt in a specific ratio is formed on the surface of the nickel substrate.

[0062] In some embodiments, the DC current density of the electrodeposition treatment I is 20-100 mA / cm 2 , for example 20, 30, 40, 50, 60, 70, 80, 90, 100 mA / cm 2 the voltage is 2-10V, for example, any value among 2, 3, 4, 5, 6, 7, 8, 9, 10V, or a range between any two of them; the deposition time of the electrodeposition treatment I is 30-60min, for example, any value among 30min, 35min, 40min, 45min, 50min, 55min, 60min, or a range between any two of them; the temperature of the electrodeposition solution I is 60-80°C, for example, any value among 60°C, 65°C, 70°C, 75°C, 80°C, or a range between any two of them. By controlling the current density and voltage within the above ranges, the deposition amounts of iron, nickel and cobalt can be reasonably controlled, which helps to ensure the uniformity of element deposition, avoid affecting the stability of the deposited layer and the substrate, and improve the electrochemical stability; by controlling the above electrodeposition time, the thickness of the deposited layer, the grain size of the deposited metal elements, the porosity, etc. can be reasonably controlled, thereby reasonably controlling the mechanical properties, electrochemical properties, etc. of the electrode; by controlling the temperature of the above electrodeposition solution within the above range, the solution conductivity, electrodeposition rate, chemical reaction rate, etc. can be reasonably controlled to obtain a better deposition layer quality, thereby making the electrode have better catalytic activity, corrosion resistance and stability.

[0063] In some embodiments, the concentration of the electrodeposition solution I is 0.1-0.5 mol / L, for example, any value among 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, or any range between two values; the mass ratio of the iron salt, the nickel salt, and the cobalt salt is (2-5): (3-10): (1-10), in which the mass ratio of the iron salt is any value among 2, 3, 4, and 5, the mass ratio of the nickel salt is 3, 4, 5, 6, 7, 8, 9, and 10, and the mass ratio of the cobalt salt is 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10; wherein the iron salt is ferric nitrate or Ferric chloride; nickel salt is nickel nitrate or nickel chloride; cobalt salt is cobalt nitrate or cobalt chloride; platinum material is platinum plate or platinum mesh; by controlling the concentration of the electrodeposition solution I, a reasonable electrodeposition rate can be guaranteed, the quality and structure of the deposition layer as well as the electrochemical stability during the deposition process can be promoted; by controlling the mass ratio of the three metal salts, the ratio between the deposition amounts of the three metals on the nickel substrate can be controlled, and by adopting the ratio between the above metal salts, a composite metal layer formed by iron, nickel and cobalt in a specific ratio can be deposited on the nickel substrate; designing the mass ratio of the three metal elements can make iron, nickel and cobalt play a maximum synergistic role, so as to make the electrode have better corrosion resistance, catalytic activity and stability.

[0064] In some embodiments, in step S3, the electrodeposition treatment II adopts a three-electrode system, wherein the nickel substrate loaded with the composite metal is used as the working electrode, graphite is used as the counter electrode, saturated calomel is used as the reference electrode, and a platinum salt solution is used as the electrodeposition solution II. By adopting the three-electrode system, the deposition effect of platinum metal on the surface of the first material layer on the surface of the nickel substrate can be better controlled, the amount of platinum deposition can be accurately controlled, and the catalytic activity, electrode structure stability and corrosion resistance of the electrode can be promoted.

[0065] In some embodiments, the weight ratio of the total weight of the iron salt, the nickel salt and the cobalt salt to the platinum salt is (100-500):1; for example, any value among 100:1, 200:1, 300:1, 400:1, 500:1 or any range value between two of them. By controlling the weight ratio of iron, nickel, cobalt and platinum, a specific ratio is formed between the four metals, and each of them can give full play to its anti-corrosion, catalytic activity and other effects. Each active metal has a good synergistic effect, which can improve the catalytic activity, corrosion resistance and structural stability of the final electrode.

[0066] In some embodiments, the DC current density of the electrodeposition treatment II is 10 to 50 mA / cm 2 , such as 10, 20, 30, 40, 50 mA / cm 2any value in the range of 2, 3, 4, 5, 6, 7, 8, 9, 10V or any value in the range of 2, 3, 4, 5, 6, 7, 8, 9, 10V; the deposition time of the electrodeposition treatment II is 50 to 150 min, for example, any value in the range of 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150 min or any value in the range of 150 min; the temperature of the electrodeposition solution II is The temperature is 30°C to 60°C, for example, any value among 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, or any range between two thereof; the molar concentration of the electrodeposition solution II is 0.001 to 0.01M, for example, any value among 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01M, or any range between two thereof.

[0067] By controlling the current density, voltage, deposition time, deposition temperature, and deposition liquid concentration, the deposition process parameters are adjusted to form a better match and synergy, so as to reasonably control the deposition rate, conductivity, chemical reaction rate, etc., and thus obtain the best deposition layer quality, ensuring that the electrode has better catalytic activity, corrosion resistance and stability.

[0068] In some embodiments, the platinum salt solution is at least one of potassium chloroplatinate solution, ammonium chloroplatinate solution, potassium chloroplatinite solution, sodium chloroplatinite solution, ammonium chloroplatinite solution and chloroplatinic acid solution. The above platinum salt is selected as the electrodeposition solution, which can better generate a reduction reaction on the surface of the nickel substrate to obtain a metal platinum deposition layer.

[0069] According to the third aspect of the present application, a method for producing hydrogen from alcohol-containing wastewater is provided, wherein electrodes are used to electrolyze alcohol-containing wastewater, wherein the cathode electrode reduces hydrogen ions in the wastewater to hydrogen gas, and the anode electrode converts alcohol oxides in the wastewater into acid; wherein the cathode electrode is the above-mentioned electrode, and the anode electrode is a graphite electrode. By using the water electrolysis system composed of the above-mentioned cathode, acid can be obtained while producing hydrogen by electrolysis, and the acid can be reused, while alcohol is not easy to be recycled and processed, thereby achieving the effect of processing alcohol and producing hydrogen at the same time.

[0070] According to a fourth aspect of the present application, there is provided application of the above electrode or the electrode prepared by the above preparation method in hydrogen production from alcohol-containing wastewater.

[0071] In the present application, the electrode with better catalytic activity, corrosion resistance and stability is used as the cathode for producing hydrogen from alcohol-containing wastewater, and water can be electrolyzed to produce hydrogen. Due to the high catalytic activity of the electrode, the hydrogen production efficiency can be improved; the anode electrolysis oxidizes the alcohol into acid to obtain acid-usable materials. The energy consumption of this process is lower than the energy consumption of electrolyzing water to evolve oxygen. Therefore, when electrolyzing alcohol-containing wastewater to produce acid, the energy consumption of cathode hydrogen production is also reduced, which can achieve the key parameters such as reducing the unit energy consumption of producing hydrogen from alcohol-containing wastewater.

[0072] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0073] The raw materials used in the examples of this application are all prior art and commercially available.

[0074] Example 1

[0075] (1) Nickel foam cutting: Take a 0.5 mm thick nickel foam roll and cut it into 1.5 cm wide strips with scissors;

[0076] (2) Treatment of the oxide layer on the surface of the nickel foam: Add an appropriate amount of 3M hydrochloric acid solution into a beaker, put the nickel foam sheet cut above into it, stir it gently to prevent the nickel foams from sticking to each other, seal the beaker with a sealing film, let it stand for 60 minutes, then take it out to obtain the pretreated nickel foam;

[0077] (3) Electrodeposition of iron, nickel and cobalt: A two-electrode system was used, wherein the working electrode was the pretreated nickel foam of step (2) (clamped by a platinum wire electrode), and the auxiliary (counter) electrode was a platinum plate electrode; deionized water, 2 g of ferric nitrate, 3 g of nickel nitrate and 1 g of cobalt nitrate were added to the reactor, and stirred evenly to prepare an electrodeposition solution I with a concentration of 0.1 mol / L; during the electrodeposition process, the DC power supply current density was 20 mA / cm 2 , voltage 2V, keep the reaction liquid temperature at 60°C, take out after deposition for 30 minutes, wash thoroughly with deionized water and dry in an oven at 60°C to obtain a foamed nickel with deposited composite metal;

[0078] (4) Modification of nickel foam for depositing composite metals: A three-electrode electrodeposition system is used, wherein the working electrode is the nickel foam electrode for depositing composite metals obtained by clamping a platinum sheet electrode in step (3), the counter electrode is a 2 cm x 2 cm graphite sheet electrode, and the reference electrode is a saturated calomel electrode; 0.06 g of potassium chloroplatinate is added to water and stirred evenly to prepare a potassium chloroplatinate solution with a concentration of 0.001 M as the electrodeposition solution; during the electrodeposition process, the deposition current density is 10 mA / cm 2, voltage 2V, keep the reaction liquid temperature at 30℃, after deposition for 50min at this temperature, take out the electrode and rinse it with deionized water and anhydrous ethanol several times, dry it in an oven at 60℃ and store it. It was detected that the thickness of the iron-nickel-cobalt composite metal layer on the surface of the nickel foam is 2mm, the thickness of the metal platinum layer on the composite metal layer is 0.02mm, the particle size of each metal is 0.1~0.4μm, and the metal structure of the nickel foam deposition is as follows Figure 1 As shown in SEM picture.

[0079] Example 2

[0080] (1) Nickel foam cutting: Take a 1 mm thick nickel foam roll and cut it into 5 cm wide strips with scissors;

[0081] (2) Treatment of the oxide layer on the surface of the nickel foam: The nickel foam obtained in step (1) is placed in a tube furnace, a protective atmosphere (90% argon, 10% hydrogen) is introduced, and the temperature is increased at a rate of 5°C / min until it reaches 500°C, and then annealed; the nickel foam after annealing is cleaned with deionized water and anhydrous ethanol and fully dried;

[0082] (3) Electrodeposition of iron, nickel and cobalt: A two-electrode system was used, wherein the working electrode was the pretreated nickel foam of step (2) (clamped by a platinum wire electrode), and the auxiliary (counter) electrode was a platinum plate electrode; deionized water, 3 g of ferric nitrate, 4 g of nickel nitrate and 3 g of cobalt nitrate were added to the reactor, and stirred evenly to prepare an electrodeposition solution I with a concentration of 0.2 mol / L; during the electrodeposition process, the DC power supply current density was 40 mA / cm 2 , voltage 4V, keep the reaction liquid temperature at 65°C, take out after deposition for 40min, wash thoroughly with deionized water and dry in an oven at 60°C to obtain nickel foam with deposited composite metal;

[0083] (4) Modification of nickel foam for depositing composite metals: A three-electrode electrodeposition system was used, wherein the working electrode was the nickel foam electrode for depositing composite metals obtained by clamping a platinum sheet electrode in step (3), the counter electrode was a 5 cm x 5 cm graphite sheet electrode, and the reference electrode was a saturated calomel electrode; 0.05 g of potassium chloroplatinate was added to water and stirred evenly to prepare a potassium chloroplatinate solution with a concentration of 0.003 M as the electrodeposition solution; during the electrodeposition process, the deposition current density was 20 mA / cm 2 , voltage 4V, keep the reaction liquid temperature at 40℃, after deposition for 70min at this temperature, take out the electrode and rinse it with deionized water and anhydrous ethanol several times, dry it in an oven at 60℃ and store it. It was detected that the thickness of the iron-nickel-cobalt composite metal layer on the surface of the nickel foam was 3.5mm, the thickness of the metal platinum layer on the composite metal layer was 0.03mm, and the particle size of each metal was 0.2-0.5μm.

[0084] Example 3

[0085] (1) Nickel foam cutting: Take a 2 mm thick nickel foam roll and cut it into 5 cm wide strips with scissors;

[0086] (2) Treatment of the oxide layer on the surface of the nickel foam: Add an appropriate amount of 6M hydrochloric acid solution into a beaker, put in the nickel foam sheet cut above, gently stir to prevent the nickel foams from sticking to each other, seal the beaker with a sealing film, let it stand for 30 minutes and then take it out to obtain the pretreated nickel foam;

[0087] (3) Electrodeposition of iron, nickel and cobalt: A two-electrode system was used, wherein the working electrode was the pretreated nickel foam of step (2) (clamped by a platinum wire electrode), and the auxiliary (counter) electrode was a platinum plate electrode; deionized water, 4 g of ferric nitrate, 5 g of nickel nitrate and 5 g of cobalt nitrate were added to the reactor, and stirred evenly to prepare an electrodeposition solution I with a concentration of 0.3 mol / L; during the electrodeposition process, the DC power supply current density was 60 mA / cm 2 , voltage 6V, keep the reaction liquid temperature at 70°C, take out after deposition for 45 minutes, wash thoroughly with deionized water and dry in an oven at 60°C to obtain a foamed nickel with deposited composite metal;

[0088] (4) Modification of nickel foam for depositing composite metals: A three-electrode electrodeposition system was used, wherein the working electrode was the nickel foam electrode for depositing composite metals obtained by clamping a platinum sheet electrode in step (3), the counter electrode was a 5 cm x 5 cm graphite sheet electrode, and the reference electrode was a saturated calomel electrode; 0.045 g of potassium chloroplatinate was added to water and stirred evenly to prepare a potassium chloroplatinate solution with a concentration of 0.005 M as the electrodeposition solution; during the electrodeposition process, the deposition current density was 30 mA / cm 2 , voltage 6V, keep the reaction liquid temperature at 45℃, after deposition for 90min at this temperature, take out the electrode and rinse it with deionized water and anhydrous ethanol several times, dry it in an oven at 60℃ and store it. It was detected that the thickness of the iron-nickel-cobalt composite metal layer on the surface of the nickel foam was 5mm, the thickness of the metal platinum layer on the composite metal layer was 0.05mm, and the particle size of each metal was 0.3-0.6μm.

[0089] Example 4

[0090] (1) Nickel foam cutting: Take a 5 mm thick nickel foam roll and cut it into 5 cm wide strips with scissors;

[0091] (2) Treatment of the oxide layer on the surface of the nickel foam: The nickel foam obtained in step (1) is placed in a tube furnace, a protective atmosphere (90% argon, 10% hydrogen) is introduced, and the temperature is increased at a rate of 10°C / min until it reaches 500°C, and then annealed; the nickel foam after annealing is cleaned with deionized water and anhydrous ethanol and fully dried;

[0092] (3) Electrodeposition of iron, nickel and cobalt: A two-electrode system was used, wherein the working electrode was the pretreated nickel foam of step (2) (clamped by a platinum wire electrode), and the auxiliary (counter) electrode was a platinum plate electrode; deionized water, 5 g of ferric nitrate, 7 g of nickel nitrate and 7 g of cobalt nitrate were added to the reactor, and stirred evenly to prepare an electrodeposition solution I with a concentration of 0.4 mol / L; during the electrodeposition process, the DC power supply current density was 80 mA / cm 2 , voltage 8V, keep the reaction liquid temperature at 75°C, take out after deposition for 50min, wash thoroughly with deionized water and dry in an oven at 60°C to obtain nickel foam with deposited composite metal;

[0093] (4) Modification of nickel foam for depositing composite metals: A three-electrode electrodeposition system was used, wherein the working electrode was the nickel foam electrode for depositing composite metals obtained by clamping a platinum sheet electrode in step (3), the counter electrode was a 5 cm x 5 cm graphite sheet electrode, and the reference electrode was a saturated calomel electrode; 0.048 g of potassium chloroplatinate was added to water and stirred evenly to prepare a potassium chloroplatinate solution with a concentration of 0.008 M as the electrodeposition solution; during the electrodeposition process, the deposition current density was 40 mA / cm 2 , voltage 8V, keep the reaction liquid temperature at 55℃, after deposition for 100min at this temperature, take out the electrode and rinse it with deionized water and anhydrous ethanol several times, dry it in an oven at 60℃ and store it. It was detected that the thickness of the iron-nickel-cobalt composite metal layer on the surface of the foamed nickel was 5.7mm, the thickness of the metal platinum layer on the composite metal layer was 0.06mm, and the particle size of each metal was 0.35-0.7.

[0094] Example 5

[0095] (1) Nickel foam cutting: Take a 5 mm thick nickel foam roll and cut it into 5 cm wide strips with scissors;

[0096] (2) Treatment of the oxide layer on the surface of the nickel foam: Add an appropriate amount of 4.5 M hydrochloric acid solution into a beaker, put in the nickel foam sheet cut above, gently stir to prevent the nickel foams from sticking to each other, seal the beaker with a sealing film, let it stand for 40 minutes and then take it out to obtain the pretreated nickel foam;

[0097] (3) Electrodeposition of iron, nickel and cobalt: A two-electrode system was used, wherein the working electrode was the pretreated nickel foam of step (2) (clamped by a platinum wire electrode), and the auxiliary (counter) electrode was a platinum plate electrode; deionized water, 5 g of ferric nitrate, 10 g of nickel nitrate and 10 g of cobalt nitrate were added to the reactor, and stirred evenly to prepare an electrodeposition solution I with a concentration of 0.5 mol / L; during the electrodeposition process, the DC power supply current density was 100 mA / cm 2, voltage 10V, keep the reaction liquid temperature at 80℃, take out after deposition for 55min, wash thoroughly with deionized water and dry in an oven at 60℃ to obtain nickel foam with deposited composite metal;

[0098] (4) Modification of nickel foam for depositing composite metals: A three-electrode electrodeposition system is used, wherein the working electrode is the nickel foam electrode for depositing composite metals obtained by clamping a platinum sheet electrode in step (3), the counter electrode is a 5 cm x 5 cm graphite sheet electrode, and the reference electrode is a saturated calomel electrode; 0.05 g of potassium chloroplatinate is added to water and stirred evenly to prepare a potassium chloroplatinate solution with a concentration of 0.01 M as the electrodeposition solution; during the electrodeposition process, the deposition current density is 50 mA / cm 2 , voltage 10V, keep the reaction liquid temperature at 60℃, after deposition for 120min at this temperature, take out the electrode and rinse it with deionized water and anhydrous ethanol several times, dry it in an oven at 60℃ and store it. It was detected that the thickness of the iron-nickel-cobalt composite metal layer on the surface of the nickel foam was 6.8mm, the thickness of the metal platinum layer on the composite metal layer was 0.08mm, and the particle size of each metal was 0.42-0.8μm.

[0099] Example 6

[0100] (1) Nickel foam cutting: Take a 5 mm thick nickel foam roll and cut it into 5 cm wide strips with scissors;

[0101] (2) Treatment of the oxide layer on the surface of the nickel foam: Add an appropriate amount of 5M hydrochloric acid solution into a beaker, put in the nickel foam sheet cut above, gently stir to prevent the nickel foams from sticking to each other, seal the beaker with a sealing film, let it stand for 35 minutes and then take it out to obtain the pretreated nickel foam;

[0102] (3) Electrodeposition of iron, nickel and cobalt: A two-electrode system was used, wherein the working electrode was the pretreated nickel foam of step (2) (clamped by a platinum wire electrode), and the auxiliary (counter) electrode was a platinum plate electrode; deionized water, 3.5 g of ferric nitrate, 6.5 g of nickel nitrate and 5 g of cobalt nitrate were added to the reactor, and stirred evenly to prepare an electrodeposition solution I with a concentration of 0.5 mol / L; during the electrodeposition process, the DC power supply current density was 80 mA / cm 2 , voltage 8V, keep the reaction liquid temperature at 80°C, take out after deposition for 45 minutes, wash thoroughly with deionized water and dry in an oven at 60°C to obtain a foamed nickel with deposited composite metal;

[0103] (4) Modification of nickel foam for depositing composite metals: A three-electrode electrodeposition system is used, wherein the working electrode is the nickel foam electrode for depositing composite metals obtained by clamping a platinum sheet electrode in step (3), the counter electrode is a 5 cm x 5 cm graphite sheet electrode, and the reference electrode is a saturated calomel electrode; 0.1 g of potassium chloroplatinate is added to water and stirred evenly to prepare a potassium chloroplatinate solution with a concentration of 0.01 M as the electrodeposition solution; during the electrodeposition process, the deposition current density is 50 mA / cm 2 , voltage 10V, keep the reaction liquid temperature at 60℃, after deposition for 130min at this temperature, take out the electrode and rinse it with deionized water and anhydrous ethanol several times, dry it in an oven at 60℃ and store it. It was detected that the thickness of the iron-nickel-cobalt composite metal layer on the surface of the nickel foam was 7.5mm, the thickness of the metal platinum layer on the composite metal layer was 0.09mm, and the particle size of each metal was 0.45-0.9μm.

[0104] Example 7

[0105] The difference between Example 7 and Example 6 is that the platinum salt added in step (4) is ammonium chloroplatinate, weighing 0.15g, preparing a 0.01M ammonium chloroplatinate solution, the reaction liquid temperature is 50°C, and the deposition time is 150min. It is detected that the thickness of the iron-nickel-cobalt composite metal layer on the surface of the nickel foam is 8.0mm, the thickness of the metal platinum layer on the composite metal layer is 0.1mm, and the particle size of each metal is 0.5-1μm.

[0106] Comparative Example 1

[0107] The difference between Comparative Example 1 and Example 6 is that the deposition solution I in step (3) contains 3.5 g of ferric nitrate and 6.5 g of nickel nitrate, but does not contain cobalt nitrate.

[0108] Comparative Example 2

[0109] The difference between Comparative Example 2 and Example 6 is that the deposition solution I in step (3) contains 6.5 g of nickel nitrate and 5 g of cobalt nitrate, but does not contain iron nitrate.

[0110] Comparative Example 3

[0111] The difference between Comparative Example 3 and Example 6 is that the deposition solution I in step (3) contains 3.5 g of iron nitrate and 5 g of cobalt nitrate, but no nickel nitrate; and the weight of potassium chloroplatinate in step (4) is 0.08 g.

[0112] Comparative Example 4

[0113] The difference between Comparative Example 4 and Example 6 is that step (4) is not included and platinum element is not deposited on the surface of the nickel foam.

[0114] Application Examples

[0115] The electrodes prepared in Examples 1 to 7 and Comparative Examples 1 to 4 were used as cathodes, graphite electrodes were used as anodes, HgO / Hg was used as reference electrodes, and alcohol-containing wastewater was used as electrolyte to form a hydrogen production system by electrolyzing alcohol-containing wastewater; and the hydrogen evolution overpotential of each electrolysis system was tested.

[0116] Table 1

[0117] sample Current density Hydrogen evolution overpotential mV Example 1 <![CDATA[100mA / cm 2 ]]> 135 Example 2 <![CDATA[100mA / cm 2 ]]> 139 Example 3 <![CDATA[100mA / cm 2 ]]> 145 Example 4 <![CDATA[100mA / cm 2 ]]> 149 Example 5 <![CDATA[100mA / cm 2 ]]> 158 Example 6 <![CDATA[100mA / cm 2 ]]> 187 Example 7 <![CDATA[100mA / cm 2 ]]> 177 Comparative Example 1 <![CDATA[100mA / cm 2 ]]> 224 Comparative Example 2 <![CDATA[100mA / cm 2 ]]> 219 Comparative Example 3 <![CDATA[100mA / cm 2 ]]> 237 Comparative Example 4 <![CDATA[100mA / cm 2 ]]> 298

[0118] It can be seen from the test results in Table 1 that the electrodes prepared in Examples 1 to 7 of the present application are used in hydrogen production from alcohol-containing wastewater, and the hydrogen evolution overpotential is 135 to 187; the electrodes prepared in Comparative Examples 1 to 4 have a hydrogen evolution overpotential of 219 to 298 in hydrogen production from alcohol-containing wastewater; by comparison, it can be seen that the hydrogen evolution overpotential of the electrodes in Examples 1 to 7 of the present application in hydrogen production from alcohol-containing wastewater is significantly lower than that in Comparative Examples 1 to 4, and is even only 50% of that in Comparative Example 4; it can be seen that the electrodes prepared in Examples 1 to 7 of the present application have higher catalytic activity, which can improve the efficiency of hydrogen production from alcohol-containing wastewater; and, since specific iron, nickel, cobalt, and platinum are selected as the active metal layer, the corrosion resistance of the electrode can be improved; further, the metal layers are deposited on the nickel substrate by electrodeposition, and the metal has stronger adhesion on the electrode, which can increase the stability of the electrode.

[0119] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0120] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. An electrode, characterized in that: The electrode includes a nickel substrate, a first material layer is attached to the surface of the nickel substrate, and a second material layer is attached to the surface of the first material layer; wherein the material of the first material layer is a composite metal formed by metal iron, metal nickel and metal cobalt; and the material of the second material layer is metal platinum.

2. The electrode according to claim 1, characterized in that The nickel substrate is nickel foam or nickel mesh; And / or, the thickness of the nickel substrate is 0.2 to 5.0 mm; And / or, the thickness of the first material layer is 1 to 8 mm; and / or, the thickness of the second material layer is 0.01 to 0.1 mm; and / or, the particle size of the metal iron, the metal nickel or the metal cobalt is 0.1 to 1 μm; And / or, the particle size of the metal platinum is 0.1-0.5 μm.

3. A method for preparing an electrode according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: Step S1: using a nickel substrate as an electrode substrate, and pretreating the nickel substrate to obtain a pretreated nickel substrate; Step S2: using electrodeposition treatment I to simultaneously deposit metallic iron, metallic nickel and metallic cobalt on the surface of the pretreated nickel substrate to obtain a nickel substrate loaded with composite metals; Step S3: using electrodeposition treatment II to deposit metal platinum on the surface of the nickel substrate loaded with the composite metal to obtain the electrode.

4. The method for preparing an electrode according to claim 3, characterized in that: In the step S1, the nickel substrate is nickel foam or nickel mesh; the thickness of the nickel substrate is 0.2 to 5.0 mm; And / or, the pretreatment includes process I or process II; The process I comprises: placing the nickel substrate in an acid solution for static treatment to remove the oxide layer on the surface of the nickel substrate; The process II comprises: annealing the nickel substrate in a protective atmosphere to remove an oxide layer on the surface of the nickel substrate; Preferably, in the process I, the acid solution is a hydrochloric acid solution; the molar concentration of the hydrochloric acid solution is 3 to 6 M, and the treatment time is 30 to 60 min; Preferably, in the process II, the heating rate of the annealing treatment is 5-10°C / min, the temperature of the annealing treatment is 450-550°C, and the treatment time is 1.5-3h; Preferably, in the process II, the protective atmosphere is composed of 85% to 95% argon and 5% to 15% hydrogen, calculated in volume percentage.

5. The method for preparing an electrode according to claim 3 or 4, characterized in that: In the step S2, the electrodeposition treatment I adopts a two-electrode system, wherein the nickel substrate is used as the working electrode; the platinum material is used as the counter electrode; and the mixed solution of iron salt, nickel salt, cobalt salt and water is used as the electrodeposition solution I.

6. The method for preparing an electrode according to claim 5, characterized in that: The DC current density of the electrodeposition treatment I is 20-100 mA / cm 2 , voltage is 2~10V; And / or, the deposition time of the electrodeposition treatment I is 30 to 60 minutes; and / or, the temperature of the electrodeposition solution I is 60-80° C.; and / or, the molar concentration of the electrodeposition solution I is 0.1 to 0.5 mol / L; And / or, the mass ratio of the iron salt, the nickel salt and the cobalt salt is (2-5):(3-10):(1-10); And / or, the iron salt is ferric nitrate or ferric chloride; And / or, the nickel salt is nickel nitrate or nickel chloride; And / or, the cobalt salt is cobalt nitrate or cobalt chloride; And / or, the platinum material is a platinum plate or a platinum mesh.

7. The method for preparing an electrode according to any one of claims 3 to 6, characterized in that: In the step S3, the electrodeposition treatment II adopts a three-electrode system, wherein the nickel substrate loaded with the composite metal is used as the working electrode; graphite is used as the counter electrode; saturated calomel is used as the reference electrode; and a platinum salt solution is used as the electrodeposition solution II.

8. The method for preparing an electrode according to claim 7, characterized in that: The DC current density of the electrodeposition treatment II is 10-50 mA / cm 2 , voltage is 2~10V; And / or, the deposition time of the electrodeposition treatment II is 50 to 150 min; and / or, the temperature of the electrodeposition solution II is 30° C. to 60° C.; and / or, the molar concentration of the electrodeposition solution II is 0.001 to 0.01 mol / L; And / or, the weight ratio of the total weight of the iron salt, the nickel salt and the cobalt salt to the platinum salt is (100-500):1; And / or, the platinum salt solution is at least one of potassium chloroplatinate solution, ammonium chloroplatinate solution, potassium chloroplatinite solution, sodium chloroplatinite solution, ammonium chloroplatinite solution and chloroplatinic acid solution.

9. A method for producing hydrogen from alcohol-containing wastewater, characterized in that: The electrodes for electrolyzing water in the hydrogen production method include an anode electrode and a cathode electrode; wherein the cathode electrode is the electrode according to claim 1 or 2 or an electrode prepared by the preparation method according to any one of claims 3 to 8, and the anode electrode is a graphite electrode.

10. Use of the electrode according to claim 1 or 2 or the electrode prepared by the preparation method according to any one of claims 3 to 8 in hydrogen production from alcohol-containing wastewater.